Following training accumulated and Almtozaa in the performance level of skill beating overwhelming without a step and jump step in Volleyball - Hikmet, Asmaa (Journal of Physical Education, 2011)
Skill is considered the core of performance thus it requires researches and studies in training styles to uplift the level of performance. Two styles are used to uplift the level of performance and they are whole and varied training. These two styles depend on the relationship between work and rest period which is considered an important variable that directly affect the development of skill. Spike requires achieving results through good performance. Aims of the research: 1. Designing a program using whole and varied training to develop spiking skill in volleyball. 2. Identifying the effect of whole and varied training on the level of performing spike in volleyball. 3. Identifying the differences between the two styles in level of performing spike in volleyball. Hypotheses of the research: 1) Whole and varied training styles positively affect the level of performing spike in volleyball. 2) There are statistical difference among pretests and posttests for both experimental groups in favor of posttests. 3) There are statistical differences in the level of performing spiking in volleyball. The researcher used the experimental method. The subjects were (20) students. The results showed that the best style for developing spiking is whole training style